Tooth Resorption – Part 1: The evolvement, rationales and controversies of tooth resorption. Issue 4 (12th May 2022) - Lin, Shaul; Moreinos, Daniel; Kaufman, Arieh Y.; Abbott, Paul V.
Abstract: In 1966, Andreasen and Hjørting‐Hansen were the first to describe a relationship between tooth resorption and dental trauma. However, Andreasen's original classification did not include other resorptive processes which have since been identified. Numerous articles have been published suggesting new terminology and definitions for tooth resorption. A uniform language with universally accepted terminology is crucial to eliminate the multiplicity of terms and definitions which only cause confusion within the profession. An electronic literature search was carried out in the PubMed database using the following keywords for articles published in English: "root resorption, " "inflammatory root resorption, " "replacement resorption, " "cervical resorption, " "trauma, " "ankylosis, " "surface resorption, " and "internal resorption." The search also included textbooks and glossaries that may not have surfaced in the online search. This was done to identify articles related to tooth resorption and its etiology in dentistry. The aim of this review was to present the history that has led to the variety of terms and definitions for resorption. This review emphasizes the need for a clearer, simpler, and more comprehensive nomenclature for the various types of tooth resorption which are presented in Part 2 of this series.